2012
DOI: 10.1111/j.1751-1097.2012.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed UV‐C Disinfection of Escherichia coli With Light‐Emitting Diodes, Emitted at Various Repetition Rates and Duty Cycles

Abstract: A 2010 study exposed Staphylococcus aureus to ultraviolet (UV) radiation and thermal heating from pulsed xenon flash lamps. The results suggested that disinfection could be caused not only by photochemical changes from UV radiation, but also by photophysical stress damage caused by the disturbance from incoming pulses. The study called for more research in this area. The recent advances in light‐emitting diode (LED) technology include the development of LEDs that emit in narrow bands in the ultraviolet‐C (UV‐C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 18 publications
(23 reference statements)
2
15
0
Order By: Relevance
“…In a study by Wengraitis et al, 20 Escherichia coli biofilms exposed using UV-C LEDs showed a change in sensitivity with duty cycle. Results showed a fourfold increase in sensitivity as the duty cycle dropped from 90% to 10%, suggesting a strong correlation between duty cycle and bacterial inactivation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study by Wengraitis et al, 20 Escherichia coli biofilms exposed using UV-C LEDs showed a change in sensitivity with duty cycle. Results showed a fourfold increase in sensitivity as the duty cycle dropped from 90% to 10%, suggesting a strong correlation between duty cycle and bacterial inactivation.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed a fourfold increase in sensitivity as the duty cycle dropped from 90% to 10%, suggesting a strong correlation between duty cycle and bacterial inactivation. 20 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations